The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1109/tit.2019.2956922
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Optimal Construction of a Loss Function Without Spurious Local Minima for Solving Quadratic Equations

Abstract: The problem of finding a vector x which obeys a set of quadratic equations |a ⊤ k x| 2 = y k , k = 1, · · · , m, plays an important role in many applications. In this paper we consider the case when both x and a k are real-valued vectors of length n. A new loss function is constructed for this problem, which combines the smooth quadratic loss function with an activation function. Under the Gaussian measurement model, we establish that with high probability the target solution x is the unique local minimizer (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…Surprisingly, we are able to prove that there are only a finite number of saddles and they are all strict saddles with very high probability. Our analysis provides a rigorous explanation for the robust performance of the PGD in solving the phase retrieval problem as a low-rank optimization problem, a phenomenon that has been observed in previous applications reported in the literature [41]. Although our primary focus is the low-rank matrix manifold, the asymptotic convergence to the minimum and the escape of strict saddles (strict critical submanifolds) are also valid on any arbitrary finite dimensional Riemannian manifold.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…Surprisingly, we are able to prove that there are only a finite number of saddles and they are all strict saddles with very high probability. Our analysis provides a rigorous explanation for the robust performance of the PGD in solving the phase retrieval problem as a low-rank optimization problem, a phenomenon that has been observed in previous applications reported in the literature [41]. Although our primary focus is the low-rank matrix manifold, the asymptotic convergence to the minimum and the escape of strict saddles (strict critical submanifolds) are also valid on any arbitrary finite dimensional Riemannian manifold.…”
supporting
confidence: 53%
“…To ensure asymptotic convergence of the PGD to the global minimizer, it remains to rule out local minimizers and identify other critical points as strict saddles. Previous works [41], [57] have shown that phase retrieval has no spurious local minimum at least with high probability in the Euclidean setting. The analysis of saddles has been more complicated because of the stochasticity and Euclidean space parameterization.…”
mentioning
confidence: 94%
See 3 more Smart Citations